Surgeon volume impact on outcomes and cost of adrenal surgeries. Issue 10 (October 2016) - Al-Qurayshi, Z.; Robins, R.; Buell, J.; Kandil, E.
Abstract: Introduction: The number of adrenal surgeries performed in the United Stated is continuing to increase. Identifying factors associated with favorable outcomes can have a major impact on cost-differences. We aim to assess the impact of surgeon volume on both clinical outcomes and cost following adrenal surgery. Materials and methods: A cross-sectional analysis was performed utilizing data from the Nationwide Inpatient Sample, 2003–2009. Surgeon volumes included (adrenalectomies/year): low-volume (1), intermediate-volume (2–6), and high-volume (≥7). Results: A total of 7045 patients were included. Surgeries performed by low-volume surgeons were associated with a higher risk of postoperative complications [OR: 1.66, 95% CI: (1.23, 2.24)]. During the study period, if all operations performed by low-volume surgeons were selectively referred to intermediate-volume surgeons, a 7.7% cost savings would have been incurred. Potential savings were even higher (8.1%) if the operations had been performed by the high-volume surgeons. With the conservative assumption that there are 5000 adrenalectomies per year in the United States, the high-volume surgeons would produce savings of 8.8 million over a span of 14 years. Conclusion: A surgeon's expertise is associated with favorable outcomes. Our model estimates that considerable cost savings are attainable with appropriate referrals to high volume endocrine surgeons.